2020
DOI: 10.1042/bsr20200158
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-21-3p modulates FGF2 to facilitate influenza A virus H5N1 replication by refraining type I interferon response

Abstract: Background: Influenza A virus (IAV) has greatly affected public health in recent decades. Accumulating data indicated that host microRNAs (miRNAs) were related to IAV replication. The present study mainly focused on the effects of microRNA-21-3p (miR-21-3p) on H5N1 replication. Methods: The levels of miR-21-3p, virus structural factors (matrix 1 (M1), nucleoprotein (NP)), type I interferon (IFN) response markers (IFN-β, IFN-α), IFN-stimulated genes (protein kinase R (PKR), myxovirus resistance A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
0
10
0
1
Order By: Relevance
“…Zhang et al ( 40 ) showed that miR-146a was significantly upregulated during IAV infection and miR-146a downregulation led to a significant reduction in IAV replication by enhancing the type-I IFN response. Shi et al ( 41 ) found that miR-21-3p downregulated fibroblast growth factor 2 expression to accelerate IAV replication by impairing the IFN response. The current study demonstrated that IAV infection modulated the expression profile of miRNA in host cells.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al ( 40 ) showed that miR-146a was significantly upregulated during IAV infection and miR-146a downregulation led to a significant reduction in IAV replication by enhancing the type-I IFN response. Shi et al ( 41 ) found that miR-21-3p downregulated fibroblast growth factor 2 expression to accelerate IAV replication by impairing the IFN response. The current study demonstrated that IAV infection modulated the expression profile of miRNA in host cells.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidences indicate that the host microRNAs (miRNAs) have a significant effect on the comprehensive host-pathogen interaction [ 7 ], even participating in the viral life cycle. For instance, miR-101 represses feline herpesvirus 1 reproduction by targeting cellular suppressor of cytokine signaling 5 to promote IFN-I signaling [ 20 ]; miR-7 suppresses rotavirus replication via targeting viral NSP5 directly [ 21 ]; miR-122 reduces HBV gene expression and replication via binding with hepatitis B virus pre-genomic RNA sequence [ 22 ]; miR-21-3p promotes influenza A virus H5N1 replication by regulating FGF2 to repress IFN-I signaling [ 23 ]; miR-545 promotes enterovirus 71 propagation through directly targeting phosphatase and tensin homolog and tumor necrosis factor receptor-associated factor 6 [ 24 ]. In the case of FMDV, there are only a few studies, artificial miRNA targeting 3D polymerase is efficient to inhibit FMDV replication [ 25 ], miR-1307 and miR-203a repress FMDV infection [ 2 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some respiratory viruses have been reported to induce miRNAs implicated in viral replication and immune response modulation [22]. Some examples include influenza A virus (IAV) [7,7,[23][24][25][26][27][28], human respiratory syncytial virus (HRSV) [15,[29][30][31][32][33][34], human metapneumovirus (HMPV) [15,21], adenovirus (ADV) [35], and due to the global health crisis miRNAs have been studied recently in SARS-CoV-2 infection [36].…”
Section: Mirnas and Their Role In Respiratory Viral Infection Immunitymentioning
confidence: 99%
“…On the other hand, IAV H5N1 diminishes levels of miR-21–3p in infected patients and A549 cells. miR-21–3p, downregulates IFN response (IFN-β, IFN-α, PKR, MxA, and OAS) by targeting the regulating fibroblast growth factor 2 (FGF2) [ 28 ]. It has also been shown that IAV H5N1 downregulates the miRNA family (30-a, -b, -c, -d, and -e) in cell lines.…”
Section: Mirnas and Their Role In Respiratory Viral Infection Immunitymentioning
confidence: 99%